Web-Based Personalized Learning Media for Enhancing Cognitive Abilities of Vocational High School Students in Basic Programming Subject - Damayanti, Tiara Ayu; Prabawa, Harsa Wara; Rahman, Eka Fitrajaya (Jurnal Guru Komputer, 2022)
Every student has different personal needs and characteristics and those must be considered as the factors that must be considered in the learning process. Therefore, appropriate learning methods must be student-centered, otherwise known as personalized learning. This study aims to implement web-based learning media with a personalized learning approach to improve cognitive abilities of vocational school students, measure the effect of media application and student responses to learning media. This study uses a quantitative method with a comparative causal design, and the Whole Life Cycle method is used for media development. The research design used was a one-group pretest-posttest. Web-based learning media with a personalized learning approach that was developed and got a percentage score of 86% or "Very Good" by experts on media testing. The use of web-based media with the personalized learning approach can improve the cognitive abilities of vocational students who are tested with post-test questions with an increase in the average N-gain of students in group A of 0.47 (which is in the "medium" category) and in group B an increase in the average N-gain of students by 0.53 (which is included in the "medium" category). There is a relationship between student responses to instructional media and an increase in n-gain at the lower-, middle-, and upper-class levels. For the overall response of students to learning media get a percentage score of 94.43%.